Pruritus der Kopfhaut - Beigi, Minaya; Weisshaar, Elke (Der Hautarzt, 2017)
Scalp pruritus is a frequent symptom and can be caused by dermatologic diseases, contact allergies, neurologic, psychiatric/somatoform and systemic diseases. In daily clinical practice scalp pruritus is a diagnostic and therapeutic challenge, especially if no detectable lesions are present. A detailed patient history and the inspection of scalp and the skin of the whole body are essential for diagnosis. Depending on the clinical findings, further dermatological diagnostic tests, laboratory analysis, imaging techniques and, where necessary, an interdisciplinary specific diagnostic check-up should be performed. Therapy comprises the treatment of the underlying disease, symptomatic antipruritic treatments such as topical treatment and if applicable systemic treatment. All this should be performed considering the individual situation especially the patient’s hair growth and density.